Regional financial performance evaluation in the Indonesian fiscal decentralization era - Joko Tri Haryanto (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
Under the decentralization policy, regions have the rights and obligations in arranging of themselves. Then many studies showed positive and negative impacts of fiscal decentralization in Indonesia. Regarding on this issue, this study was conducted in analyzing financial performance under fiscal decentralization. The analytical method used is the ratio indicator degree of fiscal decentralization, financial regional self-sufficiency indicator ratios and harmony indicator ratios of regional budget. From the degree of fiscal decentralization, in Indonesia from 2008 to 2014 has not yet been able to realize the aspects of the region's autonomy. Judging from the distribution per region, most of the regions in Indonesia are in a class of regions with less degree of fiscal decentralization. Meanwhile, indicators of local financial independence in Indonesia from 2008 to 2014 saw a significant increase. From the indicators of harmony expenses are still very dominant from the routine expenditure almost 70% -80% annually. From this result, mandatory for the local government to continue their improvement of the region's autonomy, especially in terms of funding through a mechanism that does not burden the private and public sectors.